Pilot survey of norovirus in Northern Italy: an example of surveillance of norovirus gastroenteritis. Issue 3 (8th January 2018) - Pagani, E.; Folli, F.; Tofani, S.; Ruggeri, F. M.; Ostanello, F.; Di Bartolo, I.
Abstract: In this study, we describe the results of virological investigations carried out on cases of gastroenteritis reported in different communities within a 2-year pilot surveillance programme (January 2012 to December 2013) in the autonomous province of Bolzano (Northern Italy). Among the 162 norovirus (NoV)-positive cases out of 702 cases investigated, 76 were grouped in nine suspected outbreaks, 37 were hospital-acquired and 49 were community-acquired sporadic cases. NoV infections were found in all age groups in outbreak and community-acquired cases, while the highest peak of hospital-acquired infections occurred in the elderly. Sequence analyses helped to identify suspected outbreaks both in the community and in hospital wards. Although GII.4 is the predominant genotype, sequence data confirmed that at least seven genotypes circulate causing sporadic cases. Findings in this study confirmed the relevance of NoV infections as a cause of outbreaks, and impact of NoV infections in community-acquired sporadic cases in adults that are rarely described because of a lack of reporting.